Pendekatan Antropologis Dalam Pemahaman Hadis: Studi Atas Peziarah di Makam Eyang Mahmud - Afghoni Afghoni (Diroyah : Jurnal Studi Ilmu Hadis, 2016)
Grave pilgrimage is one recommendation contained in the Hadith, grave pilgrimage itself aims to remind people to death. Hadith’s that talks about grave pilgrimage contained in the books of hadith, especially kutub al-sittah (principal six books of Hadith). As a whole, the quality of Hadith’s who discussed grave pilgrimage is authentic. The intention in revealing the content of a Hadith, then it can be achieved with the Hadith’ comment concerned. In this activity against a Hadith can use some other disciplines as an approach, as long as a branch of science that is used has been linked to the theme of the Hadith which will disyarah. One approach that can be used is an anthropological approach, which can be used to uncover the values of tradition that lives according to the times, circumstances and culture of a society. One of the grave phenomenon is a bustling pilgrimage at the tomb of Mahmud grandparents who were on home Makam Mahmud, Mekar Rahayu, District Marga Asih Bandung regency. The pilgrims at the tomb of Mahmud own grandparents still pay attention to prescriptions and prohibitions when pilgrimages grave contained in the Hadith